Thinking of Incentivizing Care? The Effect of Demand Subsidies on Informal Caregiving and Intergenerational Transfers - Joan Costa-i-Font; Sergi Jimenez-Martin; Cristina Vilaplana (Center for Economic Studies and ifo Institute (CESifo), 2016)
We still know little about what motivates the informal care arrangements provided in old age. The introduction of demand-side subsidies such as unconditional caregiving allowances (cash benefits designed either to incentivize the provision of informal care, or compensate for the loss of employment of informal caregivers) provide us with an opportunity to gain a further understanding of the matter. In this paper we exploit a quasi-natural experiment to identify the effects of the inception in 2007 (and its reduction in 2012) of a universal caregiving allowance on both the supply of informal care, and subsequent intergenerational transfer flows. We find evidence of a 30% rise in informal caregiving after the subsidy, and an increase (reduction) in downstream (upstream) intergenerational transfers of 29% (and 15%). Estimates were heterogeneous by income and wealth quantiles. Consistently, the effects were attenuated by a subsequent policy intervention; the reduction of the subsidy amidst austerity cuts in 2012.
Keywords: I18; D14; G22; 330; caregiving; intergenerational transfers; difference-in-differences; long-term care; family transfers; exchange motivation; caregiving allowances; demand-side subsidies